2011
DOI: 10.1016/j.energy.2010.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and parameter optimization of a combined sugar and ethanol production process integrated with a CHP system

Abstract: a b s t r a c tThe combined sugar and ethanol production process from sugar cane is a paradigmatic application for energy integration strategies because of the high number of hot and cold streams involved, the external hot utility requirement at two temperature levels for juice evaporation and crystallization, and the electricity demand for juice extraction by milling. These conditions make it convenient to combine the sugar-cane process with a CHP system fuelled by bagasse, the main by-product from juice extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 26 publications
2
27
0
1
Order By: Relevance
“…A conversão da canade-açúcar em açúcar ou em etanol é composta por uma série de processos físicos e químicos que acontecem em subsistemas básicos que podem ser otimizados (MORANDIN et al, 2011).…”
Section: O Processo Produtivo Da Agroindústria Canavieiraunclassified
“…A conversão da canade-açúcar em açúcar ou em etanol é composta por uma série de processos físicos e químicos que acontecem em subsistemas básicos que podem ser otimizados (MORANDIN et al, 2011).…”
Section: O Processo Produtivo Da Agroindústria Canavieiraunclassified
“…This cellular viability is essential in fermentation processes with yeast cell recycling, which depend on maintaining yeast cells alive until the end of the fermentation process, because they need to be reused over 6 to 8 months (Amorim et al, 2011). In order to be used as a fuel, the ethanol concentration must be at least 95 • GL, resulting in substantial energy consumption for purification of the fermentation product (Morandin et al, 2011), with industrial data indicating values of between 2.2 and 2.8 kg of vapor per liter of hydrated ethanol.…”
Section: Nomenclaturementioning
confidence: 99%
“…It was shown that reducing the crude syngas recovery ratio increases the quality of depleted gas that can be used as a hot utility or further recycled in the process. The same approach has been applied in liquid biofuel production (Tock et al, 2010), combined production of sugar and bioethanol (Morandin et al, 2011), hydrogen production from lignocellulosic biomass (Tock and Maréchal, 2012), and most recently, ammonia production (Tock et al, 2015).…”
Section: Introductionmentioning
confidence: 99%